The immune-modulatory effects of a mixed herbal formula on dendritic cells and CD4+ T lymphocytes in the treatment of dust mite allergy asthma and perennial allergic rhinitis. (20th April 2016) - Yang, Sien-Hung; Yu, Chia-Li; Yang, Yi-Han; Yang, Yi-Hsun
Abstract: Objective : Asthma and allergic rhinitis are chronic inflammatory diseases of the conducting nasal airway. Traditional Chinese medicine has long been used for supplemental therapy of allergic diseases, especially asthma and allergic rhinitis. We previously reported the effects of a mixed herbal formula in patients with allergic rhinitis. However, the immune-modulatory mechanism underlying the effects of herbal medicine for the treatment of allergic diseases remains unclear. Methods : We investigated the physiologic changes in dendritic cell (DC) and CD4 + T cell activity in patients with asthma and allergic rhinitis who were treated with a mixed herbal formula composed of Xin-yi-san + Xiao-qing-long-tang + Xiang-sha-liu- jun-zi-tang. Specifically, we set up in vitro autologous or heterologous co-culture experiments between DCs and CD4 + T cells, and used flow cytometry and ELISA to analyze the expression of surface molecules on DCs and the release of cytokines by CD4 + T cells. Results : Expression of HLA-DR on DCs was suppressed following treatment with the mixed herbal formula. Surface expression of CD40, CD54 and CD86 on DCs was also attenuated after treatment. In autologous co-cultures, CD4 + T cells increased their IL-10 production while decreasing TNF-α production. In heterologous co-cultures, IL-10 secretion by T cells was enhanced, while IL-12, IL-4, IL-5 and TNF-α secretion were reduced. Conclusion : Our mixed herbal formula attenuated the allergic reaction by modifying the physiologic function of the DC–CD4 + T cell interaction. Further investigations are necessary to understand the mechanism of immune modification mediated by the mixed herbal formula.